Progressive volume reduction and long-term aneurysmal collapse following flow diversion treatment of giant and symptomatic cerebral aneurysms - Sirakova, Kristina; Penkov, Marin; Matanov, Svetozar; Minkin, Krasimir; Ninov, Kristian; Hadzhiyanev, Asen; Karakostov, Vasil; Ivanova, Irena; Sirakov, Stanimir (Frontiers in Neurology, 2022)
Background The primary goal of conventional endovascular and microvascular approaches is the clinical and radiological resolution of the symptomatic aneurysm-induced mass effect. This study assessed the volume changes and mass effect reduction due to sac shrinkage after treatment with flow diverter stents (FD) for unruptured cerebral aneurysms. Methods We analyzed retrospectively 36 symptomatic aneurysms that were larger or equal to 25 mm in diameter in patients treated at our center from January 2016 to April 2022. Radiological and clinical outcomes were analyzed, including aneurysmal volume changes and resolution of aneurysm-related symptoms. Results At 6 months, 25 aneurysms decreased in size, 2 remained unchanged, and 9 aneurysms demonstrated a post-treatment dimensional increase. At 12 months, 30 aneurysms showed a progressive radiological volume reduction. Either no change or negligible shrinkage was observed in the remaining six aneurysms. At 24 months, 32 aneurysms showed aneurysmal shrinkage by a mean 47% volume loss with respect to baseline. At the last follow-up, all 13 patients who had presented with third cranial nerve palsy showed improvements. Complete reversal of the pretreatment edematous changes was confirmed in all cases. The overall post-treatment complication rate was 8.3%, as 3 patients experienced non-fatal delayed rupture of their aneurysm. There was no mortality in this study. Conclusion Flow diversion could effectively induce progressive aneurysmal shrinkage and resolution of the mass effect associated with giant symptomatic cerebral aneurysms.